Detecting the Vegetation Change Related to the Creep of 2018 Baige Landslide in Jinsha River, SE Tibet Using SPOT Data - Guo, Xinyi; Guo, Qing; Feng, Zhongkui (Frontiers in Earth Science, 2021)
It is a vital problem to monitor the post-seismic landslides economically and effectively in high-mountain regions for the long term. The creep of landslide could cause a subtle change of the overlying vegetation growth after the earthquake, which will lead to the change of vegetation spectral characteristics in optical remote sensing data. The optical remote sensing technique can be used to monitor and locate landslide creep areas in a large range and at low cost with dense vegetation, because it is easy to obtain multi-temporal observation, multiple-scale data, and multi-spectral information. We extract and identify the vegetation change before the 2018 Baige landslide using the high-resolution optical remote sensing data. Firstly, image fusion was used to improve the accuracy of change detection. Then, vegetation coverage before the landslide was calculated. The vegetation change is identified and the spatio-temporal changes of vegetation coverage are analyzed by qualitative and quantitative methods. Our results indicate that the creep distance of the landslide is about 50 m and the vegetation in the back edge area and the main sliding area display a significant downward trend with time closing to the landslide comparing with that in the reference area. The vegetation change in the remote sensing image has a good spatio-temporal correlation with the landslide creep. This study provides a potential way and perspective for monitoring future post-seismic landslide disasters.